Building resilient infrastructure, supporting sustainable industrialization, and fostering innovation (SDG 9) in selected European countries: spatial and taxonomic analysis - Grodzicki, Tomasz; Jankiewicz, Mateusz (Bulletin of Geography. Socio-economic Series, 2024)
Sustainable Development Goals (SDGs) consist of 17 goals and 169 targets to be met by the end of 2030. Since the European Union (EU) members are also included in the 2030 Agenda for Sustainable Development set by the United Nations (UN) countries, it is vital to analyze the Sustainable Development performance of the EU economies. This paper focuses on SDG 9, which aims to build resilient infrastructure, support inclusive and sustainable industrialization, and foster innovation. This research analyzes the industry, innovation and infrastructure indicators in selected European economies. The main aim of this paper is to assess the performance of the European economies in SDG 9 and to verify whether there are any spatial dependencies among countries. Applying the taxonomic measure of development and its spatial version to the group of 29 countries from Europe shows that Sweden and Denmark were the leading countries in SDG 9 in 2013 and 2019. Eastern and South-Western Europe was characterized by the lowest level of SDG 9 in 2013 and 2019. The level of SDG 9 increased over the period 2013–2019.